Calibrated ages of M179 peat core from the USA - Zicheng Yu; Stephanie Hunt; Miriam C Jones (PANGAEA, 2021)
Calibrated ages of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.